THE USE OF SCAFFOLDING BY ENGLISH TEACHERS AT SENIOR HIGH SCHOOL IN WEST SUMATERA - Hamzah, Hamzah; Rozimela, Yenni (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2018)
This study was aimed at investigating how the English teacher used scaffolding in their daily classroom routines and whether they used the scaffolding differently. The data were collected from 20Senior High School English teachers in West Sumatera by recording their full teaching sessions. The records were transcribed orthographically from which the scaffolding strategies were identified. The findings revealed that the English teachers used 10 types of scaffoldings in their teaching with different varieties in the proportions. The experience interms of length of service did not contribute to the scaffolding choices. The experienced male teachers tended to use traditional scaffolding strategies markedly higher than novice male English teachers. The difference of the use of scaffolding strategies by the experienced female English teachers and novice was not marked, with the tendency for novice female teacher used higher propostion in traditional scaffolding. Thus, it is safe to draw a conclusion that the level of experience does not contribute to their scaffolding choices.Key words/phrases: scaffolding, classroom interaction, teacher talkPENGGUNAAN PENYANGGA PEMBELAJARAN OLEH GURU SEKOLAH MENENGAH ATAS DI SUMATERA BARAT AbstrakPenelitian ini ditujukan untuk menginvestigasi cara guru menggunakan penyangga pembelajaran di dalam kelas dan membandingkan penggunaan penyangga oleh guru yang berpengalaman dan pemula. Data dikumpulkan dari 20 guru Sekolah Menengah Atas di Sumatera Barat denga cara perekaman interaksi yang terjadi antara guru dan siswa. Rekaman tersebut dibuatkan transkrip ortografis yang menjadi sumber data tempat mengidentifikasi penyangga yang digunakan. Temuan penelitian menunjukkan bahwa guru menggunakan 10 tipe penyangga dengan variatas penggunaan yang berbeda-beda. Guru laki-laki berpengalaman, yang didasarkan pada lamanya menjadi guru, lebih banyak menggunakan penyangga tradisional dari guru pemula. Sementara, pilihan penyangga oleh guru perempuan berpengalaman tidak berbeda secara signifikan dari pilihan guru pemula. Pada kelompok guru ini, ada kecenderungan guru pemula lebih banyak menggunakan penyangga tradisional. Dengan demikian, dapat disimpulkan bahwa pengalaman yang dilihat dari lama mengajar tidak memberi sumbangan terhadap pilihan penyangga yang digunakan.Kata Kunci: penyangga pembelajaran, interaksi kelas, ujaran guru